3-Propionyl-thiazolidine-4-carboxylic acid ethyl esters: a family of antiproliferative thiazolidines. Issue 1 (9th October 2014) - Önen-Bayram, F. Esra; Buran, Kerem; Durmaz, Irem; Berk, Barkin; Cetin-Atalay, Rengul
Abstract : Modification at the 2-position of the apoptosis-inducing compound ALC 67 enables tuning of its physicochemical properties. Abstract : Cancer results from unregulated cell growth. Reactivating the process of the programmed cell death, i.e. apoptosis, is a classical anticancer therapeutic strategy. The apoptosis-inducing property of the (2 RS, 4 R )-2-phenyl-3-propionyl-thiazolidine-4-carboxylic acid ethyl ester (ALC 67) molecule has recently been discovered. We analyzed in this study the impact of the phenyl moiety of this molecule on its biological activity by synthesizing and evaluating analogues where this substituent was replaced by a series of aromatic and aliphatic groups. The results demonstrated that the molecule's antiproliferative property resisted such modifications. Thus, in addition to developing a family of thiazolidine compounds with promising anticancer properties; our investigation revealed that the second position of the thiazolidine ring can be used either to tune the physicochemical properties of ALC67 or to introduce a fluorescent tag to the structure in order to track it in cells and determine its exact molecular mechanism of action.